A Histopathological Study of the Breast Cancer Cases Registered at Benghazi Medical Center from 2016 to 2018 - Bilhassan, Naziha M.; Zoubi , Salha; Attia , Adel (Scientific Journal of University of Benghazi, 2023)
Background: Breast cancer (BRC) is the second most common cancer in the world, the most frequent cancer among women, and the leading cause of cancer death in females worldwide. Aims to study the pattern of breast cancer in all the patients who were presented to the Oncology Department at Benghazi Medical Center (BMC) from various parts of eastern Libya from the 1st of January 2016 to the 31st of December 2018. Subjects and Methods: This is a retrospective, cross-sectional and histopathological study to determine the frequency of the (BRC) malignancy type, in addition to stages and age groups. The data was collected from the Oncology Department at Benghazi Medical Center which receives cancer patients from Benghazi and the whole eastern part of Libya. Data was also collected from the Pathology Department at the Faculty of Medicine, University of Benghazi and Alnon, a private laboratory. There were 515 registered patients with breast cancer including demographic and clinic-pathological data. The data was analyzed using the SPSS Program Version 20. Results: Out of 515 breast cancer patients registered at the Oncology Department (BMC), geographically 66% were from Benghazi, followed by Albaida at 9.1%. Conclusion: The majority of cases were between 46 and 56 years old. Invasive ductal carcinoma was diagnosed among most of the cases, (Grade II and stage III. Most of the breast cancer cases collected from BMC were from Benghazi, frequency is higher among the age range (46-56) and most cases were Stage III, and grade II. Invasive ductal carcinoma is the most predominant histopathological type. Most cases were HER2 negative, ER positive and PR positive, and most cases had Ki-67 levels (21- 40%).